Ethical Issues Raised by CACREP Accreditation of Programs Within Institutions That Disaffirm or Disallow Diverse Sexual Orientations. (9th June 2016) - Smith, Lance C.; Okech, Jane E. Atieno
Abstract : The field of counseling is expatiating on counselors' religious values that conflict with the affirmation of diverse sexual orientations. There is also a germane systemic issue: the Council for Accreditation of Counseling and Related Educational Programs' practice of providing accreditation to counseling programs housed within religious institutions that disaffirm or disallow individuals with sexual minority identities. This article examines the complexities of this practice given the field's ethical mandate to affirm both religious and sexual orientation diversity.